Pendampingan Primkopti Kudus menuju Koperasi Modern yang Patuh Pajak - Budiman, Nita Andriyani; Lusianti, Dina; Indaryani, Mamik; Mulyani, Sri (PT. Karya Inovatif Nusantara, 2025)
Primer Koperasi Produsen Tempe Tahu Indonesia (Primkopti) Kudus plays a strategic role in supporting tempe and tofu producers in Kudus Regency. Primkopti is striving to transform into a modern, tax-compliant cooperative by addressing economic challenges through the digitalization of accounting systems, strengthening governance, and enhancing tax awareness. The main challenges faced include limited tax knowledge, manual financial record-keeping systems, and a lack of technology utilization in cooperative operations. Through the implemented assistance program, Primkopti has received training, discussions, and hands-on practice in applying digital-based accounting systems and understanding tax regulations. The results of this initiative have demonstrated increased tax compliance, improved financial management efficiency, and accelerated Primkopti’s transformation into a more competitive and sustainable modern cooperative.